Color-emotion associations and color preferences: A case study for residences - Manav, Banu (JOHN WILEY & SONS INC, 111 RIVER ST, HOBOKEN, NJ 07030 USA, 2007)
This study examines existing beliefs about "color" focusing on color-emotion associations by discussing how color can be used as a way of communicator to fulfill human needs in residences. Fifty people from various age groups participated in the study. They were asked to match a list of adjectives with the proper color samples from the catalogue of a quite popular color producer firm in Turkey. Results indicate that there is a strong dependency between the choice and use of green at residences. Emotional responses to colors change with value and saturation levels. According to the test results, gender and age are determining factors in the selection of achromatic black. (C) 2007 Wiley Periodicals, Inc.
Keywords: Color-Emotion Associations; Built Environment; Residence; Psychology; Quantitative-Analysis; Part II; Renk Duygu Dernekler; Yapılı Çevre; Konut; Psikoloji; Kantitatif Analiz